Strategies For Increasing Sales During The Covid-19 Pandemic In Small And Medium Micro Businesses In Tangerang Selatan City - Munarsih, Munarsih (International Journal of Social and Management Studies, 2021)
The purpose of this study is to find out strategies to increase sales, including South Tangerang City MSME actors carrying out product promotion strategies through online during the covid-19 pandemic and carrying out product innovation strategies through online during the covid-19 pandemic. The data analysis techniques used in this study are qualitative descriptive method that is descriptive does not provide treatment, manipulation or modifier on the variables studied, but describes a condition as it is. The only treatment given was the research itself, which was carried out through observation, interviews, and documentation. The results of the study show that MSME actors, especially in South Tangerang City, in the promotional strategy carried out are through e-commerce including through websites and social media (whatsapp, Instagram, facebook, and others). In addition, product innovation strategies carried out by MSME actors in South Tangerang City include: continuing to innovate by presenting the latest products. Furthermore, in online stores, the product innovation strategy is carried out by creating more online stores. This is done so that online stores are easily accessible to the wider community. So that businesses can survive during the covid pandemic and can increase sales